The Engaged Microbiologist: Bringing the Microbiological Sciences to the K–12 Community - David J. Westenberg (American Society for Microbiology, 2016)
Exposing K–12 students to cutting edge science that impacts their daily lives can bring classroom lessons to life. Citizen-science projects are an excellent way to bring high-level science to the classroom and help satisfy one of the cornerstone concepts of the Next Generation Science Standards (NGSS), “engaging in practices that scientists and engineers actually use.” This can be a daunting task for teachers who may lack the background or resources to integrate these projects into the classroom. This is where scientific societies such as the American Society for Microbiology (ASM) can play a critical role. ASM encourages its members to engage with the K–12 community by providing networking opportunities and resources for ASM members and K–12 teachers to work together to bring microbiology into the classroom. Journal of Microbiology & Biology Education